Evaluation of the microvascular density in astrocytomas in adults correlated using SPECT-MIBI - Cavalcante, Sandro Pantoja [UNESP]; Walther de Almeida, Jose Reynaldo; Clara, Carlos Afonso; Scapulatempo Neto, Cristovam; Peres, Stela Verzinhase; Moriguchi, Sônia Marta [UNESP]; Dos Santos, Marcelo Jose; Da Rocha, Euclides Timoteo [UNESP] (Spandidos Publ Ltd, 2010)
Microvascular density (MVD) may be an additional prognostic marker for astrocytomas, but the heterogeneity of these tumors limits its use. Thus, imaging examinations such as SPECT-MIBI (2-methoxyisobutyl isonitrile) may take on an indirect role in astrocytoma evaluation. The aim of this study was to evaluate MVD in astrocytomas using immunohistochemistry with anti-CD34 monoclonal antibodies. The relationship between the immunohistochemical data and the parameters obtained from SPECT-MIBI was evaluated. This cross-sectional study evaluated 48 patients with brain tumors including low-grade astrocytomas (LGAs), anaplastic astrocytomas (AAs) and glioblastoma multiformes (GBMs). Patients had been admitted to the Hospital de Cancer de Barretos - Fundação Pio XII, and underwent brain SPECT-MIBI prior to any treatment. MVD was determined under an optical microscope by counting microvessels on slides from each case. SPECT-MIBI images were analyzed visually and semiquantitatively. GBMs, AAs and LGAs represented 50, 16.7 and 33.3% of the total sample, respectively. There were 13 normal and 35 abnormal SPECT-MIBI images. Significant differences in MVD were found between AA and LGA cases (p=0.040), but not between normal and abnormal SPECT-MIBI. The mean counts from SPECT-MIBI were not correlated with MVD. Among the GBM cases, there were no significant findings, except for an increased likelihood of abnormal histological test results. MVD was related to histological grade (in AA and LGA cases) but was not correlated with SPECT-MIBI.
Keywords: microvascular density; SPECT-MIBI; astrocytomas